Rabbit as sustainable meat source: carcass traits and technological quality of meat and of mechanically deboned meat (Research, Society and Development, 2020)
This study aimed to characterize rabbit carcass traits, meat quality, and mechanically deboned meat (MDRM) from New Zealand × Botucatu crossbred rabbits to determine the potential use by the meat industry. Average yields of the carcass (52.46%) and retail hind leg (33.88%), foreleg (15.51%), loin (11.63%), and back (39.83%) cuts were assessed, with total meat-to-bone ratio of 1.65. The meat proximate composition and technological characteristics pH, water retention capacity, and total collagen were similar to meat of commonly market species. Rabbit meat color was light (L* = 65.93) and with a low shade of red (C * = 19.24 and h = 52.79 °) due to the low content of heme pigments (19.89 µg acid hematin/g). The obtained MDRM met the levels of protein and fat required by Brazilian legislation, but a high calcium content (1.45% dry basis). It can be concluded that rabbits represent a viable unconventional meat resource with high potential for use in processing. In addition to raw meat, MDRM can also be obtained to be used as a meat ingredient in industrial products.